Development of Pelvic Inflammatory Disease after Ectopic Removal - Amanda Wang; Sema Hajmurad; Maryam Khan; Sarah Villarreal (Hindawi Limited, 2021)
Although ectopic pregnancy and pelvic inflammatory disease (PID) are separately commonly seen in practice, development of PID after surgical removal is rare. Here, we present the case of a 41-year-old female who was admitted for pelvic inflammatory disease diagnosed after laparoscopic salpingectomy for a ruptured ectopic pregnancy. Treatment required drainage of TOAs with interventional radiology and antibiotic treatment. This case report demonstrates how treatment of PID following ectopic pregnancy is complex and may require surgical- or radiology-guided drainage of infection in addition to common antibiotic treatment. Follow-up and duration of treatment are highlighted.